The mediating effect of allostatic load on the relationship between neighborhood perceptions and depression - Jason T. Carbone (Elsevier, 2020)
Neighborhood perceptions is an important predictor of both allostatic load in the form of biological dysregulation and major depressive disorder. Furthermore, biological dysregulation is predictive of major depressive disorder. Yet to date, the use of biological dysregulation as one potential causal pathway linking neighborhood perceptions to depression has not been explored. This study examined the relationship between neighborhood perception, biological dysregulation in the form of allostatic load, and depression among individuals who participated in the three waves of the Midlife Development in the United States study (1996-2014). Two-to-one propensity score matching was employed prior the use of causal mediation analyses. Lower neighborhood perceptions at wave one were associated with increased allostatic load at wave two. Allostatic load at wave two is associated with depression at wave three. The mediation analysis shows that 6.0% of the relationship between neighborhood perception and depression is mediated by biological dysregulation. These results can inform future prevention and treatment methods by supporting efforts to integrate individuals and community-level interventions to aid in addressing both the environmental conditions and biological factors associated with depression.